Instructional Design Based on Social Media: Developing Facebook Learning Content to Facilitate Online Student Engagement in Islamic Primary School - Yulias Prihatmoko; Kevin Herdinata Cahyadi Firdaus; Agus Wedi; Husna Qotrunnada Aysiyah (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2026)
This study aims to develop Facebook-based learning content on human and animal locomotor systems to enhance student engagement among fifth-grade students at MIN 1 Kediri. The development process employed the Sadiman model, which consists of nine stages: needs analysis, objective formulation, content development, assessment design, scriptwriting, production, testing, revision, and final product implementation. The resulting product consists of learning content uploaded to a Facebook Group, including short instructional videos and visual materials designed to support interaction and discussion. The validation results indicate that the content is highly feasible, with a score of 89% from material experts and 100% from media experts. Product trials conducted at the individual, small group, and field levels yielded scores of 85.7%, 86%, and 83%, respectively, indicating that the product is practical and suitable for online learning. Furthermore, the field trial results show that student engagement reached 83%, placing it in the high category. Therefore, Facebook-based learning content has strong potential to facilitate students’ behavioral, emotional, and cognitive engagement in the learning process.